EXPERIENCE OF FOREIGN BODY REMOVAL BY FLEXIBLE BRONCHOSCOPY IN TERTIARY CARE HOSPITAL - Hussain, Muhammad; Naqvi, Syed Mazhar Ali (Journal of Postgraduate Medical Institute, 2019)
Objective: To determine the outcome of removal of tracheobronchial foreign bodies by flexible bronchoscopy and related complications. Methodology: We retrospectively reviewed patients with foreign bodies (FBs) treated between January 2010 and May 2018 at Pulmonology department. The demographic and endoscopic data was collected and analyzed. Results: A total of 30 adult patients (12 men and 18 women) with an average age of 35 ±7.24 years were analyzed. Most common FBs included metallic pin (n=16, 53%), metallic nut-bolt (n=4, 13%), whistles (n=4, 13%), nut shells (n=2, 6%), bone (n=2, 6%), dental prosthesis (n=1, 3%) and dental brush (n=1, 3%). The prevalence of FB-related complications was 75%, including granulation formation (70%), obstructive pneumonia (20%), hemorrhage (20%), atelectasis (13%) and endobronchial stenotic scarring (10%). In 96% of the patients, the FBs were successfully removed with flexible video bronchoscopy and 01 patient required rigid bronchoscopy. Conclusion: There was high frequency of FB-related complications likely due to prolong delay between aspiration and diagnosis. The removal of foreign bodies under flexible video bronchoscopy has a significant success rate and therefore can be used in adults.